Biden Administration Trade Cooperation Platforms - S. V. Kislitsyn (Сравнительная политика)
The article examines trade policy initiatives of the Biden administration. In a complex climate of domestic political polarization, the United States compete with China and defends its position in international markets. These challenges affect the areas of high technologies, digital economy, information and communications sector, renewable energy sources, and infrastructure. At the same time, an equally important problem in the context of increased geopolitical risks remains increasing the reliability of logistics and production chains, primarily for microelectronics. Addressing these challenges requires the creation of appropriate platforms that allow the United States to interact with partner countries. Within these frameworks, the United States intends to promote the priorities of the Biden administration: standards in the field of high technologies, ensuring the energy transition, protecting working conditions and inclusion. Another crucial area is promoting the fight against corruption, ensuring transparency of business processes in partner countries and training personnel. Completing these goals should attract American business and investment to the Pacific and Indian Ocean regions and Latin America. These should also increase American leverage in its strategic competition with China. At the same time, the formats of cooperation created by the United States must be insured against their internal political situation and the risks of interruption of work when there is a change of presidential administrations. In less than four years of its work (2021–2024), the Biden administration has proposed three platforms: the Global Infrastructure and Investment Partnership, the Indo-Pacific Economic Framework for Prosperity, and the Partnership of the Americas for Economic Prosperity. The results of their implementation are different. This article examines the two last mentioned regional platforms and describes conditions for their creation, work prospects, probable risks, and some results.